2007
DOI: 10.1021/ci6005504
|View full text |Cite
|
Sign up to set email alerts
|

Understanding False Positives in Reporter Gene Assays:  in Silico Chemogenomics Approaches To Prioritize Cell-Based HTS Data

Abstract: High throughput screening (HTS) data is often noisy, containing both false positives and negatives. Thus, careful triaging and prioritization of the primary hit list can save time and money by identifying potential false positives before incurring the expense of followup. Of particular concern are cell-based reporter gene assays (RGAs) where the number of hits may be prohibitively high to be scrutinized manually for weeding out erroneous data. Based on statistical models built from chemical structures of 650 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 39 publications
(53 reference statements)
0
52
0
Order By: Relevance
“…Also fingerprint-based target prediction models, based on the WOMBAT database and Naïve Bayes models, have been applied in practice, such as to the rationalization of false positives in reporter gene assays [93]. Here it was found that false positives in reporter gene assays very often are predicted to interact with kinases involved in cell cycle progressionhence, a mechanistic hypothesis for false positives could be generated.…”
Section: Applications Of Machine Learning Based Target Prediction Metmentioning
confidence: 99%
See 1 more Smart Citation
“…Also fingerprint-based target prediction models, based on the WOMBAT database and Naïve Bayes models, have been applied in practice, such as to the rationalization of false positives in reporter gene assays [93]. Here it was found that false positives in reporter gene assays very often are predicted to interact with kinases involved in cell cycle progressionhence, a mechanistic hypothesis for false positives could be generated.…”
Section: Applications Of Machine Learning Based Target Prediction Metmentioning
confidence: 99%
“…cytotoxicity assays, where it was indeed shown that > 50% of false positives in reporter gene assays possess cytotoxic properties [93].…”
Section: Applications Of Machine Learning Based Target Prediction Metmentioning
confidence: 99%
“…For target prediction protocols, well annotated data of compound-target pairings derived from secondary assays with activity values (e.g., IC 50 , EC 50 , K d ) calculated from multiple concentration points are most useful. Single data points from highthroughput screening are less desirable, although such data has been successfully used [58,59]. Ideally, the database would have additional layers of annotation describing target family ontology (to truly be a chemogenomics database), normalized activity values, inactive as well as active compounds and data source (journal or patent citation).…”
Section: Available Databases and Desired Formatmentioning
confidence: 99%
“…Although this concept has some similarity with socalled PAINS (pan-assay interfering compounds) [10] or the older term 'frequent hitter', [11,12] non-stoichiometric inhibition does not distinguish in any way between activity in one or several assays. One of the reasons is that polypharmacology nowadays is seriously pursued as a lead finding strategy.…”
Section: Introductionmentioning
confidence: 99%
“…The latter originally referred to compounds exceeding the hit threshold due to statistical variation in the assay signal [16,17] but now is also applied to reproducible hits with undesirable mode of action. [11,[18][19][20][21][22] Non-stoichiometric inhibition in this sense should not be confused with sub-stoichiometric inhibition, a term that has also been applied to chaperone proteins [23] or antibodies, [24] which are clearly out of scope for this review.…”
Section: Introductionmentioning
confidence: 99%